The effect of a known object in a static image of a burn to improve the burn size estimation. Issue 6 (September 2021) - Smith, Kirsty; Poterlowicz, Krzystof; Southern, Stephen; Mahajan, Ajay L.; Jivan, Sharmila
Highlights: The use of photography in total burn size area estimation. Accuracy of 2D images to assess total burn size area. Methods to improve estimation of total burn surface area. Abstract: Introduction: Currently information regarding burn size from referring departments to burn centres varies in accuracy. Inaccurate assessment of burn size can lead to over or under treatment. Photographs of injuries may improve accuracy of assessment. We aimed to assess the accuracy of measuring burn size on a static image by including a standard object in the image. Methods: Simulated burn areas were drawn on different body parts of the model. Using an iPhone® model 5 s with an 8 megapixel camera we took photos of the marked area, and repeated them with the palm, a standard bank card and a penny in the picture. First the Du Bois formula, was used to calculate body surface area. Members of the Burns team were asked to view the photos ( n = 30) and estimate the percentage of the simulated burn. Results: We found an overall overestimation of burn size. Small areas of the forearm were better estimated and within 1.1% of the calculated surface area, however we found no improvement when using a standard object in these images. The back areas were most overestimated ranging from 0.9%–8.9% despite all being the same sized area. Conclusions: Static images tend to overestimate burn size despite the use of a standard object in the image.